The Efficient Capital Programme for a Maintainable Utility Level - Atsumi, H. (Review of Economic Studies, 1969)
Journal Article The Efficient Capital Programme for a Maintainable Utility Level Get access H. Atsumi H. Atsumi Osaka University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 3, July 1969, Pages 263–287, https://doi.org/10.2307/2296427 Published: 01 July 1969 Article history Received: 15 December 1967 Received: 15 December 1968 Published: 01 July 1969